Developing a National Trauma Research Action Plan (NTRAP): Results from the Pediatric Research Gap Delphi Survey - Groner, Jonathan I; Phuong, Jimmy; Price, Michelle A; Bixby, Pamela J; Ehrlich, Peter; Burd, Randall; Jensen, Aaron; Rivara, Frederick P; Sribnick, Eric; Thakkar, Rajan; Bulger, Eileen (The journal of trauma and acute care surgery, 2022)
In 2016, the National Academies of Sciences, Engineering, and Medicine trauma report recommended a National Trauma Research Action Plan (NTRAP) to "strengthen trauma research and ensure that the resources available for this research are commensurate with the importance of injury and the potential for improvement in patient outcomes." With a contract from the Department of Defense, the Coalition for National Trauma Research (CNTR) created 11 expert panels to address this recommendation, with the goal of developing a comprehensive research agenda, spanning the continuum of trauma and burn care. This report outlines the work of the group focused on pediatric trauma. Experts in pediatric trauma clinical care and research were recruited to identify gaps in current clinical pediatric trauma research, generate research questions, and establish the priority of these questions using a consensus-driven Delphi survey approach. Using successive surveys, participants were asked to rank the priority of each research question on a 9-point Likert scale categorized to represent priority. Consensus was defined as >60% agreement within the priority category. Priority questions were coded based on a dictionary of 118 NTRAP taxonomy concepts in nine categories to support comparative analysis across all panels. 37 subject matter experts generated 625 questions. 493 questions (79%) reached consensus on priority level. Of those reaching consensus, 159 (32%) were High, 325 (66%) Medium and 9 (2%) Low priority. The highest priority research questions related to surgical interventions for traumatic brain injury (ICP monitoring and craniotomy); second highest priority was hemorrhagic shock. The prehospital setting was the highest priority phase of care. This diverse panel of experts determined that most significant pediatric trauma research gaps were in traumatic brain injur, hemorrhagic shock, and the prehospital phase of care. These research domains should be top priorities for funding agencies. IV.